The Amazonas‐trap: a new method for sampling plant‐inhabiting arthropod communities in tropical forest understory. Issue 6 (3rd June 2019) - Lopes, Marta C.; Lamarre, Greg P.A.; Baraloto, Christopher; Fine, Paul V.A.; Vincentini, Alberto; Baccaro, Fabricio B.
Abstract: Methods to quantify plant‐insect interactions in tropical forests may miss many important arthropods and can be time consuming and uneven in capture efficiency. We describe the Amazonas‐trap, a new method that rapidly envelops the target plant for sampling arthropods. We evaluated the efficiency of the Amazonas‐trap by comparing it with two commonly used sampling methods to collect arthropods from plants: the beating tray and manual collection. Samples were collected in 10 permanent plots, in the Ducke forest reserve, Manaus (Amazonas, Brazil). In each plot we sampled 18 plant individuals of Protium sp. (Burseraceae): six by a beating tray, six by manual collection, and six using the Amazonas‐trap. All insects were identified to the family level and those belonging to the order Hymenoptera were identified to the species and morphospecies level. The new method sampled more insect families and more Hymenoptera species than tree beating and manual collection. Of the 75 total families collected, 20 were sampled exclusively by the Amazonas‐trap, seven were only collected with a beating tray, and seven were sampled exclusively with manual collecting. A similar pattern was found for abundance: Amazonas‐trap sampled more individuals, followed by the beating tray and manual collection. Small and winged arthropods were more abundant in Amazonas‐trap, explaining the highest richness of Hymenoptera and insect families sampled with this method. The new method sampled more spiders, wood‐fungi feeders, sap suckers, omnivorous, parasitoids, and insect predators than the other methods, but was equally effective in sampling leaf‐feeders and ants. Amazonas‐trap was more time consuming in the field, but for all diversity parameters evaluated, the new method showed better performance for collecting invertebrates on plants. Abstract : Methods to quantify herbivorous insects on plants in tropical forests can be time consuming, may miss many important arthropods, and may be uneven in capture efficiency. Here we describe the Amazonas‐trap, a new method that rapidly envelops the target plant for sampling arthropods. The Amazonas‐trap provides a more comprehensive survey of invertebrates on plants (especially if the target species are flying insects) and should be a good and cheap alternative for monitoring and ecological studies in highly diverse habitats.